The dark triad, adjustment, and age as predictors of aggression amongst South African adult male offenders in a maximum-security correctional centre - Naidoo, Kelsy (University of the Free State, 2024)
Violence and aggression are commonplace within South African correctional centres. Personality factors, adjustment to the correctional environment, and the offenders’ age may contribute to the continued aggression within the correctional environment. Many studies have confirmed the well-established relationship between the Dark Triad traits (three aversive, interrelated personality traits: narcissism, Machiavellianism and psychopathy) and aggression. However, fewer studies have explored the Dark Triad traits as predictors of aggression within the correctional environment, particularly in non-Western countries. Several studies have linked offender adjustment and age with aggression among offenders. This study aimed to investigate the individual and collective contributions of the Dark Triad traits, adjustment, and age as possible predictors of aggression amongst adult South African male maximum-security incarcerated offenders. This quantitative study sampled 366 male maximum-security offenders through convenience sampling. Using a quantitative, cross-sectional correlational design, this study investigated the relationships between the predictor and outcome variables. The data were collected using the Buss and Perry Aggression Questionnaire (BPAQ), the Dark Triad Dirty Dozen (DDTD), and the Prison Adjustment Questionnaire (PAQ). The researcher conducted a hierarchical multiple regression analysis to determine which variable(s) or set(s) of variables explain a significant percentage of the variance in aggression amongst incarcerated adult male offenders. The findings revealed that the combination of all the predictor variables, including the Dark Triad traits as a set of predictor variables, were statistically and practically significant predictors of verbal aggression, physical aggression, hostility, and anger. The results from the study can thus assist with developing appropriate rehabilitative programmes for male offenders within the correctional environment.
Dissertation(M.Soc.Sc.(Clinical Psychology))--University of the Free State, 2024
Keywords: Adjustment; Aggression; Age; Dark triad; Male offender; Maximum-security correctional centre; South Africa